Multidimensional analysis of population in Poland and Germany between 2024-2050 - Kozicki Bartosz (2024)
The following research problem was outlined in the article: how will the population of pensioners (aged 65 and over) change in 2050 compared to 2024 in Poland and Germany? The aim of the research is to attempt to conduct a multidimensional comparative analysis of data on the population in Poland and Germany between 2024 and 2050. The following research hypothesis was put forward in the study: it is assumed that the number of people in the 65+ group in 2050 in Poland and Germany will increase by at least 7 percentage points compared to 2024.